PECULIARITIES OF CONTROL OF HUMAN ALBUMIN DRUGS ON THE CONTENT OF BACTERIAL ENDOTOXINS - T. V. Kukunina; A. G. Israfilov; M. L. Romanenkova; R. S. Gaynullina; L. G. Fedko (Разработка и регистрация лекарственных средств, 2019)
The problem was considered to determine bacterial endotoxins in human albumin drugs. To improve the safety of medicines the option of dual control was recommended, which includes the rabbit pyrogen test and determining bacterial endotoxins by the LAL-test. The causes described justify the need for dual control of albumin drugs on the content of the pyrogens/bacterial endotoxins, the main of which is the special nature of the albumin molecule reversibly binding a large number of compounds, including endotoxins. There were given known causes of false-positive and false-negative reactions of the LAL-test, and sample preparation variant including dilution, temperature treatment and the use of special dispersing agents.